Silicon quantum dots inlaid micron graphite anode for fast chargeable and high energy density Li-ion batteries - Li, Huanxin; Buckingham, Mark A. (Frontiers in Chemistry, 2022)
The pursuit of rapid charging and high energy density in commercial lithium-ion batteries (LIBs) has been one of the priorities in battery research. Silicon-Carbon (Si-C), a possible substitute for graphite as an anode electrode material, is one prospect to achieving this goal. There is a debate as to whether nanoscale or the micron-scale silicon is more favourable as anode materials for LIBs. Micron-scale silicon exhibits relatively higher initial coulomb efficiency (CE) compared with nanoscale silicon, while its cycle stability is poorer. However, minimizing silicon normally benefits the cycle stability, but introduces serious side reactions, due to the large active surface for nanoscale silicon. Here, we propose silicon quantum dots (Si QDs) inlaid in micron graphite (SiQDs-in-MG) as an anode for high energy density and fast charging LIBs. The Si QDs almost eliminate the volume change typically observed in Si during long-term cycling, while the graphite blocks solvent entering the channels and contacting the SiQDs, promoting the generation of a stable solid electrolyte interphase, which is not in direct contact with the Si. SiQDs-in-MG addresses the main issues for Si-based anodes and is expected to achieve high energy density when in combination with a Lithium-Nickel-Manganese-Cobalt-Oxide (NMC) cathode in pouch cells.